Effect of oocyte vitrification before and after in vitro maturation towards Bcl-2, Bax and Bcl-2/Bax ratio expression - Zakiyatul Faizah; R. Haryanto Aswin; Hamdani Lunardhi (Majalah Obstetri dan Ginekologi, 2016)
Objectives: to compare the expression of Bcl-2, Bax and Bcl-2/Bax ratio in cumulus cell and oocyte between vitrified oocyte pre and post in vitro maturation.Materials and Methods: Maturation was operated in medium TC 100 µl for 24 hours. Vitrification begins with washing oocyte in PBS basic medium supplemented of 20% serum for 1-2 minutes, followed by equilibration medium PBS + 20% serum + 10% ethylene glycol for 10-14 minutes, then transferred to 20% serum + PBS + 0.5 M sucrose + 15% ethylene glycol + PROH 15% for 25-30 seconds. Thawing is processed by submerging the oocytes in the media: 1). PBS + 20% serum + 0.5 M sucrose, 2). PBS + 20% serum + 0.25 M sucrose, and 3). PBS + 20% serum + 0.1 M sucrose. Imunocytochemistry observed the expression of Bcl-2, bax and Bcl-2/bax ratio.Results: Bcl-2 expression on oocyte in control group differed significantly with treatment group, Bcl-2 expression on cumulus in control group differed significantly with treatment 1 group. Bax expression on oocyte in control group differed significantly with treatment group. Bax expression on cumulus in control group differed significantly with treatment group. Bcl-2/Bax expression ratio on oocyte and cumulus did not differ significantly in all groupConclusion: No difference Bcl-2/Bax expression ratio on oocyte and cumulus between vitrified oocyte pre and post in vitro maturation.